Child Begging As an Exploitative Labor Practice: A Study Of Begging Children in Unlikely, Antananarivo, Madagascar - Ramiadamahefa Tojoniaina; Solofomiarana Rapanoel Bruno Allain; Andrianjary Myriam; Rahajamanana Jasmin; Ratiarimananjatovo Narindra; Ratsimandisa Haritiana Zo; Koto-Te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR) Publisher, 2024)
This study examines child begging in Analakely, a neighborhood of the Malagasy capital, by exploring the socio-economic, cultural, and familial dynamics that perpetuate this practice. Through daily interviews with children and adults over five days, a deductive approach was used to test hypotheses based on Bourdieu's theory of genetic structuralism. The analysis reveals that children are often introduced to begging at a young age, internalizing values such as family solidarity, resourcefulness, and dignity in poverty, which reinforce their commitment to this practice. Social networks within these communities play a crucial role by providing children with the resources needed to survive and instilling in them a perception of begging as a socially and economically viable activity. This research highlights the need for an integrated and comprehensive approach to address child begging by targeting the underlying causes of this phenomenon.